A dearth of hurricanes cannot explain Maya collapse. Issue 48 (2nd December 2014) - Schultz, Colin
<x xml:space="preserve">Abstract</x> A thousand years ago the great Maya culture of Central America collapsed. Climate change was one factor that stressed the civilization until it fractured: A prolonged period of intense and persistent drought left the Maya's descendants to carry on without a robust elite urban class.